Grammatical Proficiency in Descriptive Writing: An Analysis of Tourism Vocational School Students - Purwakaluh Sri Tantra Kharisma Dewi; Kadek Sintya Dewi; Gede Mahendrayana (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This study aims to analyze the grammatical proficiency of vocational tourism school students in descriptive writing and identify the most common types of grammatical errors. Adopting a mixed-methods approach with an exploratory sequential design, the research involved 20 final-year tourism students from a vocational school in Bali. Data were collected through a descriptive writing task evaluated using a grammar assessment rubric, and semi-structured interviews were conducted to gather qualitative insights. Quantitative analysis revealed an average grammar proficiency score of 70.2 out of 100, with dominant errors found in the use of articles (26.7%), adjectives and adverbs (21.7%), and tenses (18.3%). Qualitative findings from interviews indicated challenges stemmed from confusion in applying articles, difficulties in choosing and placing descriptive vocabulary, the influence of Indonesian language structures, lack of specific descriptive vocabulary for tourism, and limited practice in creative writing. The study highlights the need for targeted interventions in grammar instruction, particularly for aspects crucial to descriptive writing, to better prepare students for the demands of the global tourism industry.